What treaty rules of CU (CES) are not consistent with the norms of the Kazakh and international law - Sarsembayev , Марат Алдангорович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2023)
The article describes the law of the Customs Union and the Common Economic Space, the norms of which do not always correspond to the recognized rules of international law and the logical rules of Kazakh law. This concerns the questions of reservations, the need to use the official languages in the development and adoption of treaties and agreements of Customs Union and the Common Economic Space, the need for rules on denunciation of the Customs Union and the Common Economic Space treaties, on the adjudicating disputes among states parties of integration, which will offer the necessary versions of solution to these issues.